Implementing digital preservation in repositories: Knowledge and practices - Pavão, Caterina Groposo (2016)
Digital preservation has to be undertaken by institutional repositories, which are responsible for the preservation of the scientific output from academic institutions. However, due to the constant evolution of the field, to gain domain knowledge and recognise best practices is a complex task for people responsible for digital preservation in those institutions. Digital preservation research, practices and solutions address specific problems, such as formats, curation, reference models, authenticity, policies and preservation plans, tools, etc., while stakeholders need an integrated, contextualized and applicable overview. This paper focuses on the implementation of digital preservation in repositories, from the perspective of the team responsible for the project, regarding the necessary knowledge and best practices. Initially, it defines and contextualizes digital preservation repositories. The following section presents a conceptual model of digital preservation, synthesized from conceptual models developed in influential projects in the field, which allows us to identify the domain knowledge in digital preservation. Finally, aspects represented in the model are discussed in the light of the performance of teams implementing digital preservation repositories. It provides recommendations, guides and examples that may be useful for the implementation of digital preservation. It points to the need to strengthen the relationship between domain knowledge in digital preservation repositories with practices developed in numerous projects developed worldwide.